Monte Carlo simulations of the S-shaped neutron guides with asymmetric concave and convex surface coatings - Souza, Alexandre P S; de Oliveira, Luiz P; Genezini, Frederico A (arXiv.org, 2021)
During the last decades, neutron beam transportation has been a well-known and established subject for designing proper neutron guides. However, sometimes unusual adaptation or adjustments are required out of original projects and after operation beginning of facilities. Inter-center transferring of instrument locations also requires a new approach that is not necessarily described in the literature. Inside these situations, the use of S-shaped guides has not been fully discussed in the literature. From a geometrical analysis, we develop a formalism of construction of a minimal S-shaped guide by only considering the exclusion of the Line-of-Sight. We study this guide model through the wavelength cutoff and the neutron transport efficiency analysis. Here, Monte Carlo simulations using MCSTAS software are applied. By intending to optimize these guide systems, simulations of this study also consider scenarios that have different supermirrors. A formalism to determine wavelength cutoff for unique and variable index guide systems is also developed. Simulation results show a good agreement between theoretical and simulated wavelength cutoff values. In addition, we have found specific configurations that combine efficient neutron transport and lower index values on the convex surfaces of curved guides that form the S-shaped guide.